2017
DOI: 10.1007/s40093-017-0159-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary graded levels of dried lemon (citrus aurantifulia) pulp on performance, intestinal morphology, and humoral immunity in broiler chickens

Abstract: Purpose Dried lemon pulp (DLP) is a by-product of fruit processing industry and is containing active antioxidants such as flavonoids, isoflavones, and flavones. Thus, current experiment was carried out to evaluate the effect of dietary graded levels of DLP on performance, intestinal morphology, and humoral immunity in broiler chickens. Methods Accordingly, a total of 280-day-old broiler chickens (Ross 308) were assigned to 4 treatments and 5 replicates of 14 chicks each. Dietary treatments included control (CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 18 publications
2
14
2
Order By: Relevance
“…In this study the pancreatic weight obtained 0.3-0.4% did not have a significant effect (P>0.05) on the weight of the pancreas. This was not different when compared to that obtained by Basir and Toghyani (2017) who obtained the results of pancreatic weight percentage in the range of 0.39 ± 0.04%.…”
Section: Treatments (%)contrasting
confidence: 57%
See 1 more Smart Citation
“…In this study the pancreatic weight obtained 0.3-0.4% did not have a significant effect (P>0.05) on the weight of the pancreas. This was not different when compared to that obtained by Basir and Toghyani (2017) who obtained the results of pancreatic weight percentage in the range of 0.39 ± 0.04%.…”
Section: Treatments (%)contrasting
confidence: 57%
“…One of the functions of the pancreas was to secrete amylase, protease and lipase enzymes that help the digestion process of carbohydrates, proteins and fats. The pancreas also produced lipolytic, amylolytic and proteolytic enzymes (Basir and Toghyani, 2017). In this study the pancreatic weight obtained 0.3-0.4% did not have a significant effect (P>0.05) on the weight of the pancreas.…”
Section: Treatments (%)contrasting
confidence: 50%
“…3. 5 % of dried lemon peels decreased daily feed intake in broiler chickens (26,30,31). It is important to note that, there are fluctuated results of Sop on growth performances.…”
Section: Growth Performancementioning
confidence: 96%
“…Furthermore, (16,17) who reported that the Sop levels of 3 to 5 % as a feed additive in broiler chickens had negative effects on growth performances. (24,25) explained that the negative effects of high dose of Sop on growth production in broiler chicken attributed to high crud fiber and pectin presented in the Sop (26). The fiber and Pectin have a deteriorating effect on GIT through increasing viscosity within intestinal tract which lower the digestive enzymes (27).…”
Section: Growth Performancementioning
confidence: 99%
“…Belhassen et al (2016) concluded that no effects of yeast supplementation on BW, FI and FCR of growing rabbits. However, Basir and Toghyani (2017) observed that BW of broilers decreased when using graded level of lemon pulp as compared to control group and FCR impaired. Also, Ezema and Eze (2015) who found that BWG and FI of rabbits increased with diets supplemented yeast.…”
Section: Growth Performancementioning
confidence: 82%